LITERATURE REVIEW: TECHNOLOGY-BASED FORMATIVE ASSESSMENT IN PHYSICS LEARNING AND ITS IMPACT ON STUDENTS' LEARNING OUTCOMES (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2025)
Physics learning requires an assessment process that not only focuses on achieving final results but also serves to support students' ongoing learning process. The form of assessment that plays a role in this is formative assessment. This literature review aims to examine formative assessment in supporting the physics learning process, particularly in terms of conceptual understanding and self-regulation. The method used in this study is a literature review by analyzing five national and international journal articles accredited by SINTA and Scopus published between 2021 and 2025. Data collection was conducted through a search of scientific databases, then articles were selected based on topic suitability, clarity of research methods, and their impact on the physics learning process. Clear, timely, and ongoing assessments help students analyze conceptual errors and increase student engagement in learning. Furthermore, the use of technology in formative assessment has been proven to provide effective feedback on student learning progress. Therefore, feedback-based formative assessment is recommended for consistent implementation to improve the quality of physics learning.